Kejahatan HAM Ras Albino Di Afrika - Prasetyo, Adi; Laksana, Agung Dwi; Ganapradipta, Masrino; Soeskandi, Hari (JHP17 (Jurnal Hasil Penelitian), 2020)
Human rights recognize forms of violation and crime, discrimination against something different is one form of violation of human rights. Africa is a large country and has many differences and gatherings of many ethnic groups and religions, it does not rule out the possibility of a conflict. In this case the albino group is often discriminated against, persecuted, bullied, raped and even killed. Ranging from babies to adults. On the basis of the background that has been written, the author will put forward a discussion about the form of what kind of human rights violations against Albino people in Africa. The method used in this journal is the Juridical Normative Method. The author uses the Juridical Normative Method to be able to find out directly in order to be able to examine how the application of the specific laws of existing international conventions about human rights violations. The results of this material discussion found that many human rights crimes were committed because of the negative stigma and myths about how albino people exist and albino people have high selling prices for spiritual needs for shamans in Africa and the black market. Discrimination against Albino people is often done even after they are born until they grow up, starting from being isolated from the surrounding environment, having difficulty getting the right to learn, the difficulty of getting the right to work, and feeling threatened if they are outside their hiding place. murder, rape, and even mutilation often occur in their lives.